Dispersed solar still for effective desalination using montmorillonite nanoparticles for sturdy clean water yield - V. Baskaran (IWA Publishing, 2021)
Direct Solar Steam Generation (DSSG) system is an emerging technique in the field of desalination for yielding sustainable clean water. This investigation propagates through the use of nanoscale absorbers (montmorillonite) for sturdy desalination because of their excellent photo thermal conversion of nanoparticles. The solar absorber was dispersed in sea water in liquid type rather than fixed or floating type. Nanoparticles of chemical composition were employed by the researchers from starting to the present day, which includes carbon nanotubes, graphene oxide, etc., Inspired by nature and keeping in mind an eco-friendly technique, here we considered montmorillonite clay nanoparticles of natural origin. The experiment was conducted for an operational period of 14 days with a yield of 5.33–6.45 kg/m2/day with an evaporation rate of 0.70, 1.42 and 4.47 kg/m2.hr under 1-, 2- and 4-sun irradiance. The clean water output parameters was validated with WHO standards to satisfy potable water characteristics. The water characteristics before desalination for turbidity, pH, and Cl–, Na+ and TDS were found to be 48.50, 8.7, and 18,400, 12,120, 20,400 mg/L respectively; after desalination they were found to be 0.30, 6.65, 12, 4.5 and 52 mg/L respectively. This work focuses on current water scarcity problem and suggest a way to survival by using naturally available, low cost material. HIGHLIGHTS A novel SSG mechanism by montmorillonite replacing carbon constituent compounds.; An eco-friendly method with reduced pollution contribution.; A low cost, stable method affordable by people belonging to lower economic standards.; A sustainable technique by the natural resources.; An additional process required in chemical based nanoparticles technique, but no further treatment for the natural based nanoparticles.;